A Bibliometric and Visualization Analysis of Human Capital and Sustainability - Surekha Rana; Pragati
The extensive and practical usage of human capital for sustainability in organizations has emerged as a popular topic in the research domain. An in-depth bibliometric analysis using VOSviewer software is used to analyse and visualize a conceptual and knowledge growth map of human capital and sustainability. Bibliometric indicators like citations are accustomed to establishing the sphere structure and the visual map to determine the research growth trends in a defined area. From January 1993 to March 2021, 573 papers were obtained through Scopus-listed journals related to human capital and sustainability. In the current article, co-citation analysis and annual trends for the top keywords are provided. Network analysis is to identify authors, publications and other research groups. Data mapping techniques diagrammatically depict the evolution of publications over time and determine trending interests in research and potential indications for future applications in achieving sustainability. Co-authorship analysis, co-citation and co-authors of the origins are also defined. In addition, country-wise quantitative analysis and temporal of publications with highly cited papers are marked and identified. The study provides analysers and practitioners with a visual and simplified frame of research on this content.